Engineering geological investigation of the Fontane landslide (Eastern Liguria, Italy) - Pepe, Giacomo; Rizzi, Giovanni; Musante, Barbara; Viola, Greta; Cevasco, Andrea (Italian journal of engineering geology and environment, 2021)
<span data-sheets-value=""1":2,"2":"This study deals with both the engineering-geological and kinematic characterization of the Fontane landslide based on geological and geophysical field investigations and on geotechnical monitoring campaigns. The coupled analysis of stratigraphic boreholes and of seismic refraction tomography profiles allowed to constrain the geometry of the landslide body. The outcomes showed that the thickness of the landslide deposit is extremely variable laterally. This observation suggested a complex morphology of the landslide bedrock surface, outlined by infilled V-shaped depressions. Such morphological concavities have been interpreted as hollows/channels carving the substratum. The investigation of the landslide motion revealed that, over the last fifteen years, the landslide kinematic was characterized by the alternation of dormant and active phases together with occasional reactivations. During the active periods, seasonal cyclic movements correlated to the local hydrological regime were found. However, through the analysis of displacement data measured by one fixed inclinometer probe, it was observed that the movements along the slip surface are not synchronous with severe rainfall events. Specifically, it was found that the displacements peaks are attained several days after the highest rainfall levels and are controlled by the increase in pore-water pressure on the slip surface. These findings suggest a delayed response of the landslide kinematic to severe rainstorms."" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">This study deals with both the engineering-geological and kinematic characterization of the Fontane landslide based on geological and geophysical field investigations and on geotechnical monitoring campaigns. The coupled analysis of stratigraphic boreholes and of seismic refraction tomography profiles allowed to constrain the geometry of the landslide body. The outcomes showed that the thickness of the landslide deposit is extremely variable laterally. This observation suggested a complex morphology of the landslide bedrock surface, outlined by infilled V-shaped depressions. Such morphological concavities have been interpreted as hollows/channels carving the substratum. The investigation of the landslide motion revealed that, over the last fifteen years, the landslide kinematic was characterized by the alternation of dormant and active phases together with occasional reactivations. During the active periods, seasonal cyclic movements correlated to the local hydrological regime were found. However, through the analysis of displacement data measured by one fixed inclinometer probe, it was observed that the movements along the slip surface are not synchronous with severe rainfall events. Specifically, it was found that the displacements peaks are attained several days after the highest rainfall levels and are controlled by the increase in pore-water pressure on the slip surface. These findings suggest a delayed response of the landslide kinematic to severe rainstorms.